THE USE OF INTERACTIVE METHODS IN TEACHING DESCRIPTIVE GEOMETRY - Yusubjonov Jonibek Farkhod ugli (Bright Mind Publishing, 2025)
Descriptive geometry has historically been regarded as one of the most fundamental and yet challenging disciplines in engineering and architecture education, serving as a foundation for the development of spatial imagination, logical reasoning, and technical drawing skills. In the contemporary educational context, the teaching of descriptive geometry faces serious challenges due to the decreasing interest of students, the rapid dominance of computer-aided design systems, and the need to adapt to new generations of learners with different learning styles and expectations. This article explores the pedagogical potential and effectiveness of interactive methods in teaching descriptive geometry to undergraduate and graduate students. Drawing upon the existing literature in mathematics education, engineering pedagogy, and educational technology, as well as a systematic review of experimental studies in classrooms across diverse institutions, the paper demonstrates that interactive approaches—such as problem-based learning, collaborative modeling, virtual visualization, gamification, and project-based exercises—significantly enhance students’ understanding and retention of spatial concepts. The study applies a mixed-method approach that integrates theoretical analysis, survey results, classroom observations, and case-based applications, aiming to show how the integration of interactive techniques can transform the teaching process from a teacher-centered mode to a student-centered paradigm. Results suggest that interactive methods foster not only knowledge acquisition but also deeper skills such as creative thinking, teamwork, and professional readiness, while addressing the challenges of digital-native learners. The findings underscore the necessity of methodological renewal in descriptive geometry pedagogy and recommend a strategic combination of traditional drawing techniques with modern interactive technologies in order to preserve the discipline’s relevance in the 21st-century educational system.
Keywords: Descriptive Geometry; Interactive Methods; Engineering Education; Spatial Imagination; Visualization; Gamification; Problem-Based Learning; Educational Technology